Managing (In)Equality through Simultaneity: Differentiation and the Rhetoric of Reform and Revolution in Higher Education (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The coronavirus pandemic has heightened the sense of crisis in higher education, initiating a reconsideration of the conditions under which transformative change actually occurs. For some historians, the radical disruption of a social system occurs under four conditions: mass mobilization warfare, transformative revolution, state failure, and lethal pandemics. However, peace aids the return of inequality and its correlate, differentiation. Differentiation produces equality and inequality in education. Dismantling this simultaneity may be impossible without radical disruption. This conditionality challenges the egalitarian impulse in the rhetoric of reform and revolution espoused by change agents in academe. This cross-disciplinary study reveals the limits of this discourse by surveying the academic models that treat differentiation as a feature rather than an anomaly in education policy.